SIMULASI PEREDAMAN GETARAN PADA PEGAS KATUP (VALVE SPRING) SISTEM HIDROLIK DENGAN METODE PID MEMANFAATKAN SIMULINK MATLAB - Keszya Wabang; Ali Warsito; Andreas Christian Louk (Universitas Nusa Cendana, 2020)
A simulation of damping vibration on valve spring hydraulic system has been done. This research is a study of the simulation that aims to control excess vibration on valve spring hydraulic system as a result of excitation force that is affected by the changes of pressure periodically, to produce a stable system. The simulation performed by using Matlab simulink with applying a PID method (P, PD, PI and PID) and noticed to variations of proportional constant (Kp), integral constant (Ki) and the derivative constant (Kd). The simulation results obtained show that by combining these three constants Ki, Kp and Kd can dampen the vibration better. For the total excitation force, using the value of Kp = 106, Ki = 7 x 106 and Kd = 6 x 104 can provide damping vibration system response on valve spring with a rise time of 1.2119 s, settling time of 1.2792 s, stable at setpoint 1, error steady state 0% and a small maximum overshoot of 0.3309. This is the result of a stable system response and best compared to the other combinations of the constant values. Keywords : vibration, damper, valve spring, hydraulic system, PID method.